2021
DOI: 10.21608/ajfm.2021.139281
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Severity of Poisoning Exposures among Patients Presented to Poison Control Center, Ain Shams University Hospitals, Egypt during 2019

Abstract: Background: Poisoning exposure continues to be an important public health concern in many developing countries and a major cause of morbidity and mortality in Egypt. The information released by the Poison Control Center of Ain Shams University Hospitals (PCC-ASUH) is mostly a trigger for increasing hazards challenging the community. Aim: To evaluate severity of poisoning exposures among patients presented to PCC-ASUH during year 2019. Methods: A retrospective study involved patients presented to the PCC-ASUH w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
0
12
1
Order By: Relevance
“…This is in harmony with the results of Hegazy and Elfiky (23) , who recorded death due to poisoning with aluminium and zinc phosphide in 60% of their deceased patients followed by organophosphates. In contrast to the present results is the result that was reported by Abdelhamid (24) where the most frequent cause of death was organophosphates 23.8% of total number of deaths. Organophosphates used to be the first cause of poisoning-related deaths in Egypt for several years as documented by the 2011-2015 Ain Shams Poison Control Center annual reports.…”
Section: Discussioncontrasting
confidence: 99%
“…This is in harmony with the results of Hegazy and Elfiky (23) , who recorded death due to poisoning with aluminium and zinc phosphide in 60% of their deceased patients followed by organophosphates. In contrast to the present results is the result that was reported by Abdelhamid (24) where the most frequent cause of death was organophosphates 23.8% of total number of deaths. Organophosphates used to be the first cause of poisoning-related deaths in Egypt for several years as documented by the 2011-2015 Ain Shams Poison Control Center annual reports.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies showed a variation in mortality rates as an outcome of acute poisoning. Abdelhamid [18] and Ali et al [19] reported mortality rates of 0.7% and 16.09% of their studied poisoned patients respectively. This difference could be explained by the difference in the poisoning severity, type of poison, time lag before treatment and availability of supportive and emergency care.…”
Section: Discussionmentioning
confidence: 93%
“…These considerations about paracetamol -as a safe medication and the decreased possibility of causing toxicity- disagree with existence of paracetamol toxicity cases in different settings; according to PPC-ASUH in Egypt, “paracetamol is one of the top ten most frequently involved exposure substances received in PCC-ASUH during 2019” [25] , [26] , Over a year (1 August 2008–31 July 2009), a survey was conducted based on acute poisoning admissions to investigate patterns in admissions and the initial management of hospital admissions for acute poisoning at Tygerberg Academic Hospital (TAH) and hospital-based poisoning consultations with the Tygerberg Poison Information Centre (TPIC) in Parow, Cape Town, South Africa. There were 662 TAH hospitalizations and 2459 hospital-based TPIC consults.…”
Section: Discussionmentioning
confidence: 99%
“…The Poison Control Center at Ain Shams University Hospitals (PCC-ASUH) is Egypt's primary poison control center. According to PPC-ASUH, “paracetamol is one of the top ten most frequently involved exposure substances received in PCC-ASUH during 2019” [25] , [26] From March 1 to June 30, 2015, a hospital-based prospective research was conducted on 653 acute poisoning cases admitted to Menoufia University Hospital's Poisoning and Addiction Control Center. Drugs poisoning represented 25.4%, and Paracetamol was 6.7% [27] .…”
Section: Introductionmentioning
confidence: 99%